2016
DOI: 10.7771/2159-6670.1140
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Source Study 2015: An Analysis of FAR Part 121 Pilots Hired after Public Law 111-216—Their Backgrounds and Subsequent Successes in US Regional Airline Training and Operating Experience

Abstract: The study collected records for 6,734 FAR Part 121 regional airline pilots to determine the effect of pilots' backgrounds on their performance in regional airline training and operations. A previous report (Bjerke et al., 2016) compared the backgrounds of these pilots (post-law pilots) to the backgrounds of pilots hired between 2005 and 2011 (pre-law pilots). This report examines the performance of post-law new-hire pilots in initial training and operations as first officers for Part 121 regional air carriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The overarching goal of these studies has been to understand how pilot backgrounds affect their performance in the regional airlines. The first ''Pilot Source Study 2010'' (Smith et al, 2010) found that ''[s]tatistically, the best performing pilots were those who had flight instructor certificates, graduated from collegiate accredited flight programs, received advanced (post-private) pilot training in college, graduated with collegiate aviation degrees (any aviation discipline), and had between 500 and 1,000 preemployment flight hours'' (p. 73). The second ''Pilot Source Study 2012'' (Smith et al, 2013) continued the work from Smith and colleagues (2010) with a different dataset and reached similar conclusions.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The overarching goal of these studies has been to understand how pilot backgrounds affect their performance in the regional airlines. The first ''Pilot Source Study 2010'' (Smith et al, 2010) found that ''[s]tatistically, the best performing pilots were those who had flight instructor certificates, graduated from collegiate accredited flight programs, received advanced (post-private) pilot training in college, graduated with collegiate aviation degrees (any aviation discipline), and had between 500 and 1,000 preemployment flight hours'' (p. 73). The second ''Pilot Source Study 2012'' (Smith et al, 2013) continued the work from Smith and colleagues (2010) with a different dataset and reached similar conclusions.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In 2010 and 2012, teams of Pilot Source Study researchers, reacting to these changes and their potential impact, collected convenience sample data from regional airlines on the source characteristics (background) of newly hired pilots and the subsequent performance of those pilots in air carrier operations, in the era before the new law (Smith, Bjerke, NewMyer, Niemczyk, & Hamilton, 2010;Smith et al, 2013). At the time of publication, the 2010 and 2012 research helped answer the following questions: Where do regional pilots come from?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to PL 111-216, the Pilot Source Study 2010 (Smith et al, 2010) collected data from six regional airlines. This study analyzed 2,156 records of pilots hired from 2005 to 2009 and found that more than half of those new-hire pilots had a baccalaureate degree with an aviation focus.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…AABI is an organization of aviation stakeholders (e.g., educators, practitioners, industry representatives, airlines, and manufacturers) that evaluates the quality of collegiate aviation programs seeking accreditation. In order to provide critical data to the ARC, AABI initiated research studies that became known as the Pilot Source Study of 2010 (Smith, Bjerke, NewMyer, Niemczyk, & Hamilton, 2010) and the Pilot Source Study of 2012 (Smith et al, 2013). Information from those studies was important in providing factual data related to the potential effects of the Pilot Certification and Qualification Requirements for Air Carrier Operations Rule (FAA, 2012), hereafter referred to as the FOQ Rule.…”
Section: Introductionmentioning
confidence: 99%